The power of live stream commerce: A case study of how live stream commerce can be utilised in the traditional British retailing sector - Kamarin Merritt; Shichao Zhao (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
As e-commerce continues to grow on a rapid scale, the rise of new technological innovations has come about, such as that of live stream commerce, which has risen rapidly throughout China through the successful case of Taobao Live. Therefore, this research project is focused on live stream retailing as an e-commerce innovation to understand how the key aspects, such as usability, functionality, interaction, and, in general, how its success can be transferred into Western society. A mixed methods approach is taken to collect the crucial data that are needed to understand the current behaviours of British consumers and to understand their preferred methods of shopping and why. This study presents robust recommendations from the collected data, providing strategic insight into the adoption of live stream retailing in the West and incorporating the development of a live stream commerce plug-in prototype that has the potential to be transferred compatibility into any business model.
Keywords: 650; British retailing sector; e-commerce; live stream; open innovation; user experience research